Libertarian easements revisited - Dominiak, Łukasz (Wydawnictwo Uniwersytetu Wrocławskiego, 2021)
In the present paper, I develop further my original argument for extending the Blockian Proviso to landlocked property. I use Walter Block’s newest rejoinder as an opportunity to generalize my case for necessity easements. I argue that in order to attenuate various conflicts of rights, libertarianism should interpret its thesis that property rights are absolute in a less demanding way.
Keywords: libertarianism; easements; the Blockian Proviso; absolute rights; conflicts of rights